2014
DOI: 10.1016/j.jiph.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Defining travel-associated cases of enteric fever

Abstract: There is no internationally recognized case-definition for travel-associated enteric fever in non-endemic countries. This study describes the patterns of case reporting between 2007 and 2011 as travel-associated or not from the surveillance data in England, Wales and Northern Ireland (EWNI), before and after a change in the time component of the case-definition in January 2011. It examines in particular the role of a time frame based on the reported typical incubation period in defining a case of travel-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…However, we defined subgroups of similar studies and found their mean incubation period to range from 9.7 days to 21.2 days. These values are within the range quoted by international organisations reporting 3 to 60 days [ 3 ], 3 to 30 days [ 12 ] and also scientific literatures reporting 10 to 20 days [ 18 ]. Some literature report shorter incubation periods than we observed, like Raffatellu et al reporting a median of 5 to 9 days [ 19 ] or 8 to 14 days [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, we defined subgroups of similar studies and found their mean incubation period to range from 9.7 days to 21.2 days. These values are within the range quoted by international organisations reporting 3 to 60 days [ 3 ], 3 to 30 days [ 12 ] and also scientific literatures reporting 10 to 20 days [ 18 ]. Some literature report shorter incubation periods than we observed, like Raffatellu et al reporting a median of 5 to 9 days [ 19 ] or 8 to 14 days [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…These values are within the range quoted by international organisations reporting 3 to 60 days [ 3 ], 3 to 30 days [ 12 ] and also scientific literatures reporting 10 to 20 days [ 18 ]. Some literature report shorter incubation periods than we observed, like Raffatellu et al reporting a median of 5 to 9 days [ 19 ] or 8 to 14 days [ 18 ]. We also identified attack rate and vaccination as possible factors that could affect the incubation period distribution.…”
Section: Discussionsupporting
confidence: 82%
“…Where the antimicrobials used to treat the case could be determined, these data were obtained. While PHE's public health guidance recommends that cases be regarded as travel-associated where symptom onset occurs within 28 days of travel [20], for the purposes of this investigation, we regarded travel within 60 days as pertinent to ascertaining the likely geographical source of an isolate. Where cases had no direct travel history but had recent, close contact with a traveller, the case was regarded as associated with that region of travel as a propagated infection.…”
Section: Enhanced Public Health Surveillance Of Enteric Fevermentioning
confidence: 99%
“…Prevention of S . Typhi infection among travelers through pre-travel vaccination is fundamental as international travel becomes more accessible and a significant cause of travel-associated illness (Freedman et al, 2014 ). Government and public health authorities are becoming more involved in promoting immunization, personal hygiene education as well as implementing GeoSentinal sites to collect surveillance data including patient demographic characteristics, detailed travel history, vaccination status, and specific typhoid fever disease diagnosis (Leder et al, 2013 ).…”
Section: Typhoid Fever a Global Problemmentioning
confidence: 99%